Investigation of Grain Characters of Some Bean Varieties in Eastern Anatolian Conditions - Leyla İdikut; Tolga Karabacak (Turkish Journal of Agriculture: Food Science and Technology)
In this study, it was aimed to investigate the quality characteristics of different dry beans (Önceler 98, Göynük 98, Yunus 90, Topçu, Aras 98, Alberto, Bermaz, Noyanbey 98, Akman 98, Göksün, Karacaşehir 98) cultivars. The research, which was planned to be 20 plants per square meter and 4 repetitions, was conducted in Eastern Anatolia (Elazig) between May and September in 2017. The grain number per plant, grain weight per the plant, 100 grain weight, protein, starch and oil ratios of bean varieties were examined. At the end of the study, the number of grains per plant, grain weight of plant, 100 grain weight, protein, starch and fat ratio of beans varieties was between 25.45-159.85 piece, 19.00-51.15 g, 21.18-49.62 g, 24.65-28.24%, 40.80-46.31% 1.02-1.77% respectively. The highest values were determined for protein ratio (%) on Noyan Bey 98 cultivar and for grain weight of plant, starch ratio, fat ratio (%) on Göynük 98 cultivar among bean varieties.